Analisa Kepuasan Pelanggan Terkait Service Quality Makeup Artist: Vallen Beauty - Shelvi Juwitasari; Alda Ramadhika (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
In the rapidly growing beauty industry, customer satisfaction is a crucial indicator of the sustainability of Makeup Artist (MUA) service businesses. This phenomenon highlights the importance of analyzing service quality as a determining factor of customer loyalty. This study aims to (1) identify the level of customer satisfaction with the services provided by Vallen Beauty, and (2) analyze customer perceptions of service quality based on the five SERVQUAL dimensions. The study adopts the SERVQUAL theoretical framework, which includes the dimensions of tangibles, reliability, assurance, responsiveness, and empathy. The research method used is descriptive qualitative with a case study approach at Vallen Beauty. Data collection was carried out using three main techniques: in-depth interviews with the owner, staff, and loyal customers, supported by direct observation of the service process and documentation in the form of reviews and portfolio. The findings reveal a high level of customer satisfaction with Vallen Beauty’s services, which significantly contributes to customer loyalty and word-of-mouth recommendations. Customer perceptions of the five SERVQUAL dimensions are consistently positive, with reliability (consistent and timely results) and empathy (warm, personal approach) identified as the main strengths. Based on these findings, it is recommended that Vallen Beauty enhance the formal aspects of its services, such as building a customer database, designing a loyalty program, and proactively communicating product credibility to strengthen long-term customer relationships.